SEJARAH DAN DINAMIKA TAFSIR AL-QUR’AN DI INDONESIA: MEMBACA AYAT-AYAT POLIGAMI DALAM TAFSIR AL-AZHAR DAN AL-MISBAH - Badrus Zaman, Akhmad Roja (Mumtaz: Jurnal Studi Al-Quran dan Keislaman, 2020)
The Qur'anic conception of polygamy is always interesting to talk about.  In the context of the Indonesian nation, the study of polygamy has long been a hot topic of conversation, even since the time of the national movement-precisely the revival of the women's movement around 1928. This article tries to read the interpretation of polygamy in Al-Azhar and Al-Misbah interpretations. The selection of these two interpretations is because each of them is considered a representation of his era, Al-Azhar's interpretation represents his dynamics with a period of national movement-Quasi Objective Traditionalists-and Al-Misbah's interpretations represent his dynamics with a period around the end of the 20th century (1998)-Modernist objectivity.  From the research conducted it can be seen that 1) Hamka and Quraish Shihab have the same interpretation, namely that polygamy is limited to ability and can be used when in certain circumstances, 2) the resurrection of women in pre-independence and post-independence times has a strong influence on the product of interpretation.  both of them, the interpretation of Hamka and Qurais Shihab present in different social spaces, and each has the aim of giving enlightenment to the people about polygamy.